2019
DOI: 10.1111/jpi.12616
|View full text |Cite
|
Sign up to set email alerts
|

The Lhx4 homeobox transcript in the rat pineal gland: Adrenergic regulation and impact on transcripts encoding melatonin‐synthesizing enzymes

Abstract: Homeobox genes generally encode transcription factors involved in regulating developmental processes. In the pineal gland, a brain structure devoted to nocturnal melatonin synthesis, a number of homeobox genes are also expressed postnatally; among these is the LIM homeobox 4 gene (Lhx4). We here report that Lhx4 is specifically expressed in the postnatal pineal gland of rats and humans. Circadian analyses revealed a fourfold rhythm in Lhx4 expression in the rat pineal gland, with rhythmic expression detectable… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
50
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
2
1

Relationship

2
4

Authors

Journals

citations
Cited by 19 publications
(61 citation statements)
references
References 45 publications
(68 reference statements)
11
50
0
Order By: Relevance
“…The transcriptomes of the photoreceptors of the retina and the pinealocyte of the pineal gland share a high degree of similarity. [8][9][10][11][12][15][16][17][18]20 Our systematic expression analyses in the current study confirm that the melatonin-producing enzymes and homeobox genes selected here are expressed in both the retina, pineal gland and cultured pinealocytes. However, while the phototransduction transcripts are known to be expressed in the retina and in the neonatal pineal gland, 6 the current study shows that genes representing all levels of the phototransduction cascade are expressed in the adult pineal gland.…”
Section: Discussionsupporting
confidence: 76%
See 3 more Smart Citations
“…The transcriptomes of the photoreceptors of the retina and the pinealocyte of the pineal gland share a high degree of similarity. [8][9][10][11][12][15][16][17][18]20 Our systematic expression analyses in the current study confirm that the melatonin-producing enzymes and homeobox genes selected here are expressed in both the retina, pineal gland and cultured pinealocytes. However, while the phototransduction transcripts are known to be expressed in the retina and in the neonatal pineal gland, 6 the current study shows that genes representing all levels of the phototransduction cascade are expressed in the adult pineal gland.…”
Section: Discussionsupporting
confidence: 76%
“…We have previously shown that homeobox genes controlling rhythmic melatonin synthesis in the rat pineal gland exhibit 24 hour rhythms themselves. 20,31,36 To determine if rhythmic expression should be considered when analysing the role of homeobox genes in the postnatal retina, diurnal and circadian gene expression was analyzed in the retina and compared to that of the pineal gland (Figure 3; Tables 3,4). Our data confirmed a prominent 3-40-fold rhythmic expression of Aanat in both the retina and the pineal gland in LD and DD, as previously reported, 7,32 whereas minor and inconsistent rhythms were detected for acetylserotonin O-methyltransferase (Asmt) and tryptophan hydroxylase 1 (Tph1) transcripts encoding the other enzymes in melatonin synthesis (Figure 3A).…”
Section: The Otx2 Crx and Lhx4 Homeobox Genes Are Rhythmic In The Pineal Gland But Not In The Retinamentioning
confidence: 99%
See 2 more Smart Citations
“…However, as a special feature of the pineal gland, a number of homeobox genes continue to be expressed into adulthood or are even restricted to the postnatal gland . To this end, we have shown that certain pineal homeobox genes are involved in transcriptional regulation of the enzymes of the melatonin synthesis pathway and that rhythmic expression of these transcription factors is also controlled by the adrenergic input to the gland …”
Section: Introductionmentioning
confidence: 98%